2000
DOI: 10.1073/pnas.97.21.11667
|View full text |Cite
|
Sign up to set email alerts
|

Amblyopes see true alignment where normal observers see illusory tilt

Abstract: Amblyopia (''lazy eye'') is an impairment in visual acuity resulting from abnormal neural development in the visual cortex. We tested the responses of ten amblyopic and six normal observers to illusions of perceived orientation in textures of Gabor patches: the ''Fraser illusion,'' the ''phase illusion,'' and a ''tilted chain'' illusion. The illusory tilt of the stimulus rows was matched by actual tilt in the opposite direction by using the method of constant stimuli. Amblyopes showed a significant increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…It is still not entirely clear whether amblyopia affects the visual pathway beyond the primary visual cortex (Barnes et al, 2001;Daw, 1998;Kiorpes & McKee, 1999), although it has been suggested that neural deficits in amblyopia are not limited to neurons in V1 (Kiorpes et al, 1998), and disruption in the binocular organization of extra-striate cortical areas has been documented in amblyopic primates (Movshon et al, 1987) and cats (Schroder, Fries, Roelfsema, Singer, & Engel, 2002). A number of psychophysical studies have also reported that amblyopia impairs visual functions that are known to involve higher cortical areas, including visual illusions (Popple & Levi, 2000), individuation of features within an image (Sharma, Levi, & Klein, 2000), second-order perception (Mansouri, Allen, & Hess, 2005;Wong, Levi, & McGraw, 2001), contour integration (Hess & Demanins, 1998;Kozma & Kiorpes, 2003;Kovács, Polat, Pennefather, Chandna, & Norcia, 2000), global motion (Simmers, Ledgeway, & Hess, 2005;Simmers, Ledgeway, Hess, & McGraw, 2003), and motion aftereffects (Hess, Demanins, & Bex, 1997). A recent functional magnetic resonance imaging study also found decreased cortical activation in response to motion stimuli in anisometropic amblyopic eyes (Bonhomme et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is still not entirely clear whether amblyopia affects the visual pathway beyond the primary visual cortex (Barnes et al, 2001;Daw, 1998;Kiorpes & McKee, 1999), although it has been suggested that neural deficits in amblyopia are not limited to neurons in V1 (Kiorpes et al, 1998), and disruption in the binocular organization of extra-striate cortical areas has been documented in amblyopic primates (Movshon et al, 1987) and cats (Schroder, Fries, Roelfsema, Singer, & Engel, 2002). A number of psychophysical studies have also reported that amblyopia impairs visual functions that are known to involve higher cortical areas, including visual illusions (Popple & Levi, 2000), individuation of features within an image (Sharma, Levi, & Klein, 2000), second-order perception (Mansouri, Allen, & Hess, 2005;Wong, Levi, & McGraw, 2001), contour integration (Hess & Demanins, 1998;Kozma & Kiorpes, 2003;Kovács, Polat, Pennefather, Chandna, & Norcia, 2000), global motion (Simmers, Ledgeway, & Hess, 2005;Simmers, Ledgeway, Hess, & McGraw, 2003), and motion aftereffects (Hess, Demanins, & Bex, 1997). A recent functional magnetic resonance imaging study also found decreased cortical activation in response to motion stimuli in anisometropic amblyopic eyes (Bonhomme et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…3,12 In addition, amblyopes show deficits in a range of visual tasks. These include hyperacuity, [13][14][15][16] shape perception, 17 contour integration, 18 spatial interaction of surrounding visual objects, 19,20 phase sensitivity, 21 visual counting, 22 pattern vision, 23 stereopsis, 24 and motionprocessing 25 deficits. Several psychophysical theories have been proposed to explain the abnormal visual perception in the amblyopic brain: (1) an increase in the size of cortical receptive fields, 13 with the peak of the SF tuning shifted to lower spatial frequencies; (2) a decrease in the contrast sensitivity of small cortical filters 10,11 ; (3) a decrease in the density of cortical neurons (i.e., undersampling) 26 ; and (4) an increase in spatial uncertainty or distortion, with the neural representation of the visual image being somewhat distorted at the cortical level.…”
mentioning
confidence: 99%
“…As a second step, these studies have scaled stimuli based on visual acuity and compensated for contrast sensitivity losses to equate the output of early visual cortex from the amblyopic eye to that of normal-vision participants. Despite a nominal match at the level of early visual cortex outputs, patients with amblyopia still show deficits on illusory tilt perception (18), contour integration (19)(20)(21)(22)(23), global motion sensitivity (8,(24)(25)(26)(27)(28), object enumeration (29), and object tracking (7,30). The impairments listed above have been interpreted to indicate that amblyopia may involve abnormalities in "higher-level" (e.g., extrastriate) neural processing that occur independent of any deficits in early processing stages (e.g., in striate cortex).…”
mentioning
confidence: 99%